Aspek Sosial Dalam Novel Swarna Alor Karya Dyah Prameswarie: Kajian Sosiologi Sastra dan Implementasi sebagai Bahan Ajar Sastra Indonesia di SMP - Puspitasari, Aprilia Mekar, Dr. Nafron Hasjim (2016)
This study aimed to (1) describe the elements that construct Swarna Alor Novel by Dyah Prameswarie, (2) decribe social aspect in Swarna Alor Novel by Dyah Prameswarie, and (3) describe the result of Swarna Alor Novel by Dyah Prameswarie. The method of this study was descriptive qualitative. The object of this study was social aspect in Swarna Alor Novel by Dyah Prameswarie. The data of this study were words, phrases, sentences, and paragraph in Swarna Alor Novel by Dyah Prameswarie. The primary source of this study was Swarna Alor Novel by Dyah Prameswarie published by Tiga Serangkai, Surakarta 2015, thick book 278 pages. The secondary data of this study were research paper, journal, and articles which relevant to this study. The technique of collecting data were read dan write. This study used triangulation theory to validate the data. This study used dialectica to analyze the data. Based on the structural analysis, the theme in Swarna Alor Novel was about two adolosence's effort who wanted make their dreams became real by work program. The characteristics in this novel were Lilo, Mbarep, Sardi, Christine, Mrs. Sariat, Mr. Libana, Samara, and Juan. The plot in Swarna Alor Novel was chronological plot. The setting in Swarna Alor Novel were place, time, and social. Social aspects in Swarna Alor Novel were family disorganization, amoral, life environment, and crime. The result of this study could be implemented in literature learning at Junior High School, based on basic competency 14.1 and 15.1 were to respond the quote of teen novel (original and translation) and explain story chronological, character, and setting of teen novel (original and translation).